Critical encounters with immersive storytelling - Gröppel-Wegener, Alke, ....-; Kidd, Jenny, ....- (New York : Routlegde, Taylor & Francis Group, 2019)
A uniquely interdisciplinary look at storytelling in digital, analogue, and hybridised contexts, this book traces different ways stories are experienced in our contemporary mediascape. It uses an engaging range of current examples to explore interactive and immersive narratives. Critical Encounters with Immersive Storytelling considers exciting new forms of storytelling that are emerging in contemporary popular culture. Here, immersion is being facilitated in a variety of ways and in a multitude of contexts, from 3D cinema to street games, from immersive theatre plays to built environments such as theme parks, as well as in a multitude of digital formats. The book explores diverse modes and practices of immersive storytelling, discussing what is gained and lost in each of these ‘genres'. Building on notions of experience and immersion, it suggests a framework within which we might begin to understand the quality of being immersed. It also explores the practical and ethical aspects of this exciting and evolving terrain.
Keywords: Storytelling